Dead end for endemic plant species? A biodiversity hotspot under pressure - Kidane, Yohannes O.; Steinbauer, Manuel; Beierkuhnlein, Carl (Global Ecology and Conservation, 2019)
Tropical high mountains are hosting important hot spots of biodiversity on small mostly remote areas. Recently, these precious ecosystems are under threat from land use change and climate change coupled with other local drivers of biodiversity loss. Along the East African Afroalpine ecosystems, area above the treeline have experienced long-term spatial isolation and extreme climatic conditions (climatic factors such as low mean temperature, diurnal freeze-thaw cycles and other energy-related factors) which lead to the formation of "Sky Island" like ecosystems that are rich in endemics and unique. The Bale Mountains of Ethiopia are home to the largest tropical alpine plateau in Africa, with no spacious high summits that provide space for upward shift of species. Here, we studied plant species diversity and distribution patterns and tested potential future impacts of climate change induced warming on those patterns. This study is based on distribution data acquired from nested circular plots along an elevational gradient ranging from 2000m asl to the highest elevation (4385 m asl). We find hump shaped species richness patterns on both aspects, i.e. the dry north-eastern and the wet monsoon exposed south-western escarpment. In addition, the proportion of endemic species increases monotonically towards the summit on all slopes. Based on our data and literature, we project future climate impact for three regional warming scenarios (+2 degrees C, + 3 degrees C and + 4 degrees C). We quantify the future range of 114 endemic plant species based on their current occurrence records applying a lapse rate of 0.6 degrees C per 100 m of elevation. We find that future climate change would significantly alter species distribution patterns with pronounced impact on the unique ecosystems and endemic species restricted to the afroalpine plateau. Very likely this will be leading to the extinction of many endemic species. Published by Elsevier B.V.
CRIS-Team WoS Importer:2019-08-09